Food allergy is associated with recurrent respiratory tract infections during childhood - Woicka-Kolejwa, Katarzyna; Zaczeniuk, Magdalena; Majak, Paweł; Pawłowska-Iwanicka, Kamila; Kopka, Monika; Stelmach, Wlodzimierz; Jerzyńska, Joanna; Stelmach, Iwona (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : To find out whether children with food allergy have an increased risk of recurrent upper and lower respiratory tract infections and of asthma. Aim: To describe the clinical profile of children diagnosed with food allergy referred to the Allergy Clinic. Material and methods : We conducted a retrospective study to assess the patients’ demographic, anthropometric and clinical data. The analysis included data of all children by the age of 10 years (registered with the Allergy Clinic between 2012 and 2013) in whom IgE mediated food allergy had been diagnosed during 18 months of observation. Results : We included 280 children into the analysis. Recurrent respiratory tract infections (rRTI), asthma and gastrointestinal (GI) symptoms were observed in 153 (54.6%), 96 (34.3%), 39 (13.9%), respectively, with a significant increasing trend across age-subgroups. In children from 1 to 2 years old, sensitization to -lactoglobulin increased the risk of rRTI (OR = 3.91; 95% CI: 1.03–14.87). In older children sensitization to allergens other than milk or egg decreases the risk of rRTI (OR = 0.25; 95% CI: 0.10–0.62); sensitization to egg decreased the risk of asthma diagnosis (OR = 0.09; 95% CI: 0.01–0.75). We did not identify food allergens which change the risk of GI symptoms in children. This finding was consistent throughout all age-subgroups. Conclusions : Sensitization to -lactoglobulin increased the risk of rRTI in children under 2 years of age nearly four times. The presence of sensitization to food allergens above 3 years of age did not increase the risk of developing clinical presentation of food allergy other than atopic dermatitis.